Changes in clients' perceptions of family planning quality of care in Kaduna and Lagos States, Nigeria: A mixed methods study - Akomolafe, Toyin O.; OlaOlorun, Funmilola M.; Okafor, Emeka; Baruwa, Sikiru; Afolabi, Kayode; Jain, Aparna (Frontiers in Global Women's Health, 2022)
Community Pharmacists (CPs) and Patent and Proprietary Medicine Vendors (PPMVs) are crucial to improving access to family planning (FP) services in Nigeria. Although the private sector is preferred for convenience, availability of commodity, privacy, and timeliness, less well known is the quality of care received by clients who obtain FP services from CPs and PPMVs. This paper seeks to explore the use of validated quality of care measures for programming in Kaduna and Lagos States and to assess how these measures worked in capturing changes in quality of care using client exit interviews implemented at two time points. Using validated measures of quality of care, 598 and 236 exit interviews in round 1 and 2 were conducted with FP clients aged 18-49 years old. The quality of care domains were assessed using 22 questions. A weighted additive quality score was created, and scores were grouped into three: low, medium, and high quality. Changes in quality of care received were examined using chi-square. A subset of 53 clients were selected for in-depth interviews in two rounds. Deductive and inductive approaches were used for coding, and data analysis was thematic. In Lagos, we observed increases in 16 out of 22 items while in Kaduna increases were only observed in 8 items. For instance, increases were observed in the proportion of women who experienced visual privacy between round 1 and 2 in Lagos (74% to 89%) and Kaduna (66% to 82%). The quality of care received by clients changed over time, women who reported high quality care in Lagos increased, 42% to 63%, unlike Kaduna with a reduction of high quality care from 35% to 21%. In-depth interviews revealed that women perceived that they were treated respectfully, felt their sessions with providers was visually private, could ask questions, and were asked about their preferred method. This study demonstrates that clients received high quality of care services from providers (CPs and PPMVs) especially in Lagos, and such services can be improved over time. Continuous support may be required to maintain and prevent reduction in quality of FP counseling and services, particularly in Kaduna.